Flexural Behaviour of Chicken Mesh Ferrocement Laminates with Partial Replacement of Fine Aggregate by Steel Slag - Sridhar Jayaprakash; Jegatheeswaran Dhanapal; Vivek Deivasigamani; Elias G (Advances in Materials Science and Engineering)
Bending tests were conducted on ferrocement laminates containing chicken mesh and steel slag. The fundamental goal of the examination was to investigate the effects of partial substitution of fine aggregate by steel slag in cement mortar combining chicken mesh of different volume fractions as reinforcement in thin ferrocement laminates. The following variables were investigated: (a) volume fraction of chicken mesh as 0.94%, 1.88%, 2.82%, and 3.77% and (b) level of steel slag substitution from 0% to 50% by weight fine aggregate. Results show that ferrocement laminates with chicken mesh of volume fractions of 3.77% and 30% substitution of fine aggregate with steel slag display better performance in terms of load deflection behaviour, first crack load, ultimate load, energy absorption, and ductility ratio when related with other specimens. An analytical model has been proposed to predict the ultimate moment carrying capacity of ferrocement laminates under flexure to validate the experimental results.